2005
DOI: 10.1007/bf03026333
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer-based delivery systems for advanced imaging and skeletal tissue-specific therapeutics

Abstract: There is considerable advantage in developing tissue-specific delivery systems for therapeutic and diagnostic applications. Synthetic water-soluble polymeric delivery systems have been developed to allow selective delivery of therapeutic and imaging agents to musculoskeletal tissues. For mineralized tissues, bone-targeting agents such as aspartic acid octapeptide could concentrate the polymer conjugates to bone surfaces including resorption sites, which was demonstrated with routine bone histomorphometry. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…We have previously demonstrated that Asp 8 or bisphosphonate conjugates of HPMA copolymers are readily incorporated into bone (6). Interestingly, however, the HPMA copolymer–Asp 8 conjugates were found in initial studies in mice to show preferential uptake on resorption surfaces (7) and a similar observation was made in the present study in aged, ovx rats. The osteotropicity of the hexapeptide of aspartic acid (Asp 6 ) was first described by Kasugai et al (19) and later this group conjugated Asp 6 to estradiol and found that the conjugate maintained a positive bone effect but minimized other side effects when compared with unconjugated estradiol (20).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We have previously demonstrated that Asp 8 or bisphosphonate conjugates of HPMA copolymers are readily incorporated into bone (6). Interestingly, however, the HPMA copolymer–Asp 8 conjugates were found in initial studies in mice to show preferential uptake on resorption surfaces (7) and a similar observation was made in the present study in aged, ovx rats. The osteotropicity of the hexapeptide of aspartic acid (Asp 6 ) was first described by Kasugai et al (19) and later this group conjugated Asp 6 to estradiol and found that the conjugate maintained a positive bone effect but minimized other side effects when compared with unconjugated estradiol (20).…”
Section: Discussionsupporting
confidence: 90%
“…Newly formed bone usually has a lower crystallinity than older bone and it is the older bone that is usually undergoing bone resorption (22). This may help explain why there was uptake of bisphosphonate-HPMA copolymer–FITC conjugates on both formation and resorption surfaces (7), whereas there was better relative uptake of Asp 8 -HPMA copolymer–FITC conjugates on resorption surfaces where more mature bone with a higher crystallinity would be exposed. This difference may provide a valuable and unique opportunity to target therapeutics to different functional bone surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation